Racial or Ethnic Health Disparities among Older Adults in Four Population Groups in South Africa - Nancy Phaswana-Mafuya; Karl Peltzer (Ubiquity Press, 2018)
Background: Racial or ethnic health disparities have been evidently apparent during the apartheid era in South Africa. This study aims to assess ethnic health disparities in four elderly population groups. Methods: Data for this study emanated from the 2008 study of "Global AGEing and adult health (SAGE) wave 1" (N = 3284) aged 50 years or older in South Africa. Associations between exposure variables and outcome variables (health status variables and chronic conditions) were examined through bivariate analyses and multivariable logistic regression. Results: Indians or Asians reported the highest prevalence of poor self-rated health (23.7%) and functional disability (11.6% and 29.1%). Coloureds had the lowest grip strength (55.3%) and Whites the highest cognitive functioning (80.1%). Coloureds had the highest prevalence of hypertension (85.0%), stroke and/or angina (15.0%), edentulism (26.8%) and low vision (50.6%); and Indians or Asians had the highest prevalence of arthritis (43.5%) and diabetes (24.4%). In adjusted analysis, Whites (Odds Ratio [OR]: 0.24, Confidence Interval [CI]: 0.11, 0.57) and Coloureds (OR: 0.50, CI: 0.29, 0.87) had lower odds of self-reported health status compared to Black Africans. Coloureds (OR: 0.36, CI: 0.22, 0.61) had lower odds of grip strength than Black Africans. Indians or Asians had higher odds of functional disability (OR: 1.87, CI: 1.03, 3.02) and diabetes (OR: 2.65, CI: 1.45, 4.83) than Black Africans. Whites (OR: 3.92, CI: 1.63, 9.41) and Coloureds (OR: 2.14, CI: 1.21, 3.78) had higher odds of cognitive functioning than Black Africans. Whites had lower odds (OR: 0.54, CI: 0.31, 0.93) and Indians or Asians had higher odds (OR: 1.91, CI: 1.91, 1.01, 3.59) of arthritis than Black Africans. Coloureds had a higher prevalence of hypertension (OR: 1.71, CI: 1.14, 2.58), stroke and/or angina (OR: 1.74, CI = 1.36, 2.22), edentulism (OR: 6.51, CI: 4.07, 10.41) and low vision (OR: 1.68, CI: 1.29, 2.19) than Black Africans. Conclusion: There are still ethnic health disparities in South Africa in the post-apartheid era (i.e., Black Africans [lower cognitive functioning], Whites [poor self-reported health status and edentulism], Coloureds [poor self-reported health status, lower grip strength, arthritis, hypertension, stroke and/or angina, edentulism and low vision], Indians or Asians [poor functional disability, arthritis and diabetes]). Understanding these ethnic health disparities may help in developing better strategies to improve health across population groups.